Penerapan Metode Certainty Factor Pada Sistem Pakar Diagnosa Penyakit Mata - Putri Masliana; Yessica Siagian; Sri Rezki Maulina Azmi (Forum Kerjasama Pendidikan Tinggi, 2022)
Eyes are one part of the body that has an important role in human life. Eyes are often also affected by a disease that causes patients to go blind. Sometimes patients often experience early symptoms of unknown disease as if these symptoms are normal. This is due to lack of information about eye diseases so that patients do not understand the initial symptoms they experience are symptoms of one of the eye diseases that often occur if left untreated for a long time, eye disease will get worse. The diagnostic process requires an expert and experienced expert in order to produce the right diagnosis. However, the limited time that an expert has sometimes becomes an obstacle for patients who will consult to solve a problem to get the best solution. So for that patients need information about the disease, the researchers created a web-based system and contained expert knowledge so that they could answer what eye diseases they experienced. make a diagnosis in order to easily treat the disease. The application designed is a web-based computer system that is integrated with databases and programming languages ​​such as PHP-MySQL so that it can help sufferers to diagnose the symptoms and types of eye diseases. The application of an expert system in making this decision by analyzing data using the Certainty Factor method to generate true and false values ​​on the new and old knowledge bases and comparing them with the weight values ​​in each frame so that the percentage of the disease type is obtained. From the results of the diagnostic process using this application, the system provides a choice of symptoms that must be answered by the patient based on the symptoms experienced by the patient, namely blurred vision such as foggy, seeing circles around light, and often changing the size of the glasses which results in cataract disease by 100% with a total value cf (Certainty) =26